2018
DOI: 10.1128/jmbe.v19i1.1511
|View full text |Cite
|
Sign up to set email alerts
|

Poster Development and Presentation to Improve Scientific Inquiry and Broaden Effective Scientific Communication Skills

Abstract: We have redesigned a tried-and-true laboratory exercise into an inquiry-based team activity exploring microbial growth control, and implemented this activity as the basis for preparing a scientific poster in a large, multi-section laboratory course. Spanning most of the semester, this project culminates in a poster presentation of data generated from a student-designed experiment. Students use and apply the scientific method and improve written and verbal communication skills. The guided inquiry format of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 17 publications
(16 reference statements)
1
21
0
2
Order By: Relevance
“…An even more positive attitude toward research and scientific methodology was previously described for fifth‐year German medical students in traditional or problem‐based curricula (Pruskil et al, 2009). Rauschenbach et al (2018) reported that 72% of students felt that their scientific writing skills had improved as a result of engaging with a scientific project.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An even more positive attitude toward research and scientific methodology was previously described for fifth‐year German medical students in traditional or problem‐based curricula (Pruskil et al, 2009). Rauschenbach et al (2018) reported that 72% of students felt that their scientific writing skills had improved as a result of engaging with a scientific project.…”
Section: Discussionmentioning
confidence: 99%
“…), might not be expected from a single project, it could still deliver valuable data in addition to the already available facts (Fang and Meyer, 2003; Solomon et al, 2003; Abu‐Zaid and Alkattan, 2013). As the method of poster production could also be applied to other pre‐clinical or clinical‐theoretical subjects, including microbiology (Rauschenbach et al, 2018), it might be conceivable that such long‐term effects will be measurable once scholarly research activities have been integrated into the teaching concepts of all undergraduate disciplines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 This application has also been shown to further enhance student experiences when their work is culminated into a poster. 16,17 However, the limited amount of literature to support the completion of projects and posters may also introduce the potential for selection bias because the authors were only able to select from a small pool of literature data. Further research is needed to fully assess this impact.…”
Section: Discussionmentioning
confidence: 99%
“…A poster presentation was scheduled at the end of the semester within the laboratory time. Poster presentations have been shown to increase student learning, engagement, and improve communication skills ( 35 37 ). Besides the common project flow, each student was assigned either a particular technique to explain in more detail such as Sanger sequencing, NGS, TOPO cloning, use of dilution curves for PCR sensitivity and linearity in amplification; or a particular type of microbes and a particular factor to assess correlation with the microbes present such as ethnicity, gender, and diet.…”
Section: Suggestion For Determing Student Learningmentioning
confidence: 99%